Molecular detection of dugbe orthonairovirus in cattle and their infesting ticks (Amblyomma and Rhipicephalus (Boophilus)) in Nigeria - Oluwafemi Babatunde Daodu; Albert Eisenbarth; Ansgar Schulz; Julia Hartlaub; James Olukayode Olopade; Daniel Oladimeji Oluwayelu; Martin H. Groschup (Public Library of Science (PLoS), 2021)
Dugbe orthonairovirus (DUGV), a tick-borne zoonotic arbovirus, was first isolated in 1964 in Nigeria. For over four decades, no active surveillance was conducted to monitor the spread and genetic variation of DUGV. This study detected and genetically characterized DUGV circulating in cattle and their infesting ticks (Amblyomma and Rhipicephalus (Boophilus)) in Kwara State, North-Central Nigeria. Blood and or ticks were collected from 1051 cattle at 31 sampling sites (abattoirs and farms) across 10 local government areas of the State. DUGV detection was carried out by RT-qPCR, and positive samples sequenced and phylogenetically analysed. A total of 11824 ticks, mostly A. variegatum (36.0%) and R. (B.) microplus (63.9%), were obtained with mean tick burden of 12 ticks/cattle. Thirty-four (32 A. variegatum and two R. (B.) microplus) of 4644 examined ticks were DUGV-positive, whereas all of the cattle sera tested negative for DUGV genome. Whole genome sequence (S, M and L segments) and phylogenetic analyses indicate that the positive samples shared up to 99.88% nucleotide identity with and clustered around the Nigerian DUGV prototype strain IbAr 1792. Hence, DUGV with high similarity to the previously characterised strain has been detected in Nigeria. To our knowledge, this is the first report of DUGV in North-Central Nigeria and the most recent information after its last surveillance in 1974. Author summary More than half a century after the discovery of a new, potentially zoonotic virus transmitted by ticks, the prevalence of Dugbe virus in cattle and its tick vector was investigated in Nigeria. The survey took place in Kwara State on the border with the Republic of Benin over a period of one year. More than 1,000 cattle were examined across the state and nearly 12,000 ticks were collected and identified under the microscope. Using established diagnostic protocols for molecular detection of Dugbe virus by quantitative PCR, we found no virus in the cattle population, but about 0.7% (n = 34) of the ticks were carriers of the virus. The overwhelming majority of ticks collected from cattle belonged to only two species: Amblyomma variegatum (tropical cattle tick) and Rhipicephalus (Boophilus) microplus (Asian blue-footed tick). In addition, most Dugbe virus infections were found in A. variegatum, and only two R. (B.) microplus were also infected. Although there is no clear evidence that A. variegatum is the main vector of Dugbe virus, our whole virus genome data showed a remarkably high similarity with Dugbe virus first isolated in Nigeria in 1964 in the same tick species.